A PHENOMENOLOGY STUDY FOR PRECIPATATING FACTOR OF AUDITORY HALLUCINATION ON PATIENT WITH SCIZOFRENIA AT MENTAL HOSPITAL IN SURABAYA - Nasrullah, Dede; Reliani; Iin Masfiyah; Sukadiono; Mundakir (International Journal of Psychosocial Rehabilitation, 2020)
An auditory hallucination is one of the typical signs of schizophrenia in which a person perceives hearing an unreal voice or whisper into reality. In Indonesia, the incidence of schizophrenia in 2013 was around 400,000 people or as many as 1.7 per 1,000 population and increased to 7 permil in 2018 including East Java Province increased from 0.22% to 0.50%. There is an increase in inpatients at Menur Mental Hospital every year from 1715 in 2016 to 2147 patients in 2017; 30% of them experiencing hallucinations. The purpose of this study was to determine the precipitation auditory hallucination factor on patients with schizophrenia at Menur Mental Hospital, East Java Province. The research method used a qualitative phenomenological research design by conducting interviews that were recorded and analyzed with the Collaizi approach. This research conducted at Flamboyan and Kenari Rooms in Menur Mental Hospital of East Java Province with a total of 15 patient as participants. From the results of the thematic analysis, four major themes of precipitating factors for auditory hallucinatory were formulated such as difficult to sleep, an uncertain state of mental anxiety, lack of social support and lack of spiritual support. Based on the results of the study, most participants experienced sleep disorders, especially at night, uncertain conditions of mind anxiety due to not being able to accept and deal with various problem situations, lack of social support in the absence of meaningful people in life and feel alone and lack of spiritual support due to lack belief in God and not doing spiritual activities. Prevention of auditory hallucination in patients with schizophrenia could do by understanding and recognizing the precipitating factors such as sleep difficulties, uncertain state of mental anxiety, lack of social support, and lack of spiritual support.